2018
DOI: 10.1111/den.13292
|View full text |Cite
|
Sign up to set email alerts
|

Japanese guidelines for peroral endoscopic myotomy: 1st edition

Abstract: This Editorial refers to the article by H. Inoue, p 563‐579 of the issue DEN 30:5.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Nevertheless, the true significance of this abnormal acid reflux may not be immediately evident and therefore long-term follow-up is recommended to evaluate for GER as well as for cancer surveillance, although currently there is no consensus regarding the frequency of these follow-up examinations. 35 What could be the potential reasons for this increased GER after POEM? To understand the reasons behind this discrepancy, let us review the anatomical basis of reflux and the evolution of AC treatment over the past 100 years.…”
Section: The Issue Of Post-poem Germentioning
confidence: 99%
“…Nevertheless, the true significance of this abnormal acid reflux may not be immediately evident and therefore long-term follow-up is recommended to evaluate for GER as well as for cancer surveillance, although currently there is no consensus regarding the frequency of these follow-up examinations. 35 What could be the potential reasons for this increased GER after POEM? To understand the reasons behind this discrepancy, let us review the anatomical basis of reflux and the evolution of AC treatment over the past 100 years.…”
Section: The Issue Of Post-poem Germentioning
confidence: 99%
“…Recently, POEM has been established as a minimally invasive method for treating achalasia (6). This treatment is effective and safe, even in elderly patients, and exhibits favorable short-and long-term prognoses (6,7). Sato et al (8) performed peroral endoscopic biopsies of the muscular layer termed POEM-b, with histopathological and immunohistochemical analysis of POEM-b samples showing signs of neurodegeneration rather than inflammatory infiltration into the muscle layer (8).…”
Section: Introductionmentioning
confidence: 99%
“…The proposed causative factors for achalasia are diverse and multifactorial, with complex interactions between autoimmune and inflammatory responses that can be initiated by viral infections in genetically susceptible patients (2). One causative agent includes the herpes simplex virus (HSV), a neurotrophic virus that predominates in squamous epithelium, varicella-zoster virus, measles virus and human papillomavirus (4,5,7,12). In addition, HSV type 1 (HSV 1) DNA and RNA have been detected in the tissues of all patients with achalasia, but not in the tissues of control subjects (13).…”
Section: Introductionmentioning
confidence: 99%
“…However, in recent years, per-oral endoscopic myotomy (POEM) has been established as an alternative minimally invasive method of treating esophageal achalasia (6). This treatment is effective and safe, even in elderly patients, allowing for short and long-term prognoses (6,7). Sato et al (8) performed per-oral endoscopic biopsies from the muscle layer during POEM, called POEM-b.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the proposed causal factors are varied and multifactorial, and are hypothesized to involve complex interactions between the autoimmune and inflammatory response, and this may be initiated by viral infections in patients who are genetically susceptible (2). Causal viral agents include (but not limited to) herpes simplex virus, which is a neurotropic virus that exhibits a predilection for squamous epithelium, as well as varicella-zoster, measles and human papillomavirus (4,5,7,10). Moreover, it has been reported that HSV type 1 (HSV-1) DNA and RNA is detectable in all tissues from patients with achalasia, but not in the control tissues (11).…”
Section: Introductionmentioning
confidence: 99%